La « théorie de l'expérience intégrale de l'immédiat » ou la quatrième voie du « feu purificateur » - Francis Farrugia (Sociologies, 2007)
The text entitled « Théorie de l'expérience intégrale de l'immédiat » is the 4th part of Georges Gurvitch’s book Morale théorique et science des mœurs, Leurs possibilités - leurs conditions. It concludes the chapter II of this book, which deals with “Present theory’s historical antecedents of moral experience”. This article, very dense due to complex epistemological considerations, has a central position in a work beginning in 1915. Written in 1937, it is thus published for the first time nearly thirty years before the last Georges Gurvitch’s book Les cadres sociaux de la connaissance. In this founding text of Georges Gurvitch’s attitude regarding experience, and particularly moral phenomenon, is clearly sketched the Georges Gurvitch’s dialectical thought process which is central in his work: the “dialectical hyperempirism”. The introduction shows premises of it, in order to demonstrate the federative strength, rather unknown, of Georges Gurvitch’s thought regarding different considerations of sociology.